National spatio-technical potential for PTES in Sweden: A first-order assessment by criteria screening - Persson, Urban; Ottermo, Fredric; Sánchez-García, Luis; Saini, Puneet; Bales, Chris (International Journal of Sustainable Energy Planning and Management, 2025)
For Sweden, a country with one of the most developed district heating sectors in the world, the continued decarbonisation of central heat supplies and the contemporary development towards lower heat distribution temperatures is generating increased interest in large-scale seasonal thermal energy storage technologies. By virtue, not only of energy storage, but also of load shifting and peak shaving capabilities, seasonal storages are recognised today as key components in highly integrated and smart energy systems but have so far seen very limited application in Sweden. Given that Denmark, neighbour to Sweden and with a district heating development on par, is a world-leader in the application of pit thermal energy storages (PTES), this paper aims to initiate investigations into the possibilities for a similar application in Sweden. A spatial analysis sequence, akin to indicator modelling, identifies suitable areas for the construction of PTES by elimination of non-suitable areas based on a set of input data parameters and associated selection criteria, all within cost-effective heat transmission distances of aggregated district heating areas. The national potential in terms of available suitable land, expressed and discussed here by two model extremes scenarios, is generally high, but with local variations and with a characteristic latitudinal difference.